Tinjauan Pengaruh Metode Granulasi Basah terhadap Stabilitas Obat dalam Sediaan Padat - Ginna Arvi Nanda; Putri Thamara Utami; Naila Awalia Antoni; Resti Aulia; Serlin Astria; Nurul Jannah; Syakira Permata Auliya; Syafira Atika Putri; Laila Nur Salam; Annisa Mutia (CV. ITTC INDONESIA, 2026)
The development of tablet dosage forms in Teknologi Farmasi requires optimal formulation to achieve products that meet pharmacopeial quality standards. Wet granulation is a widely used method due to its ability to improve flowability, compressibility, and content uniformity of tablets. Studies show that the combination of fillers such as Avicel PH 101 and lactose produces granules and tablets with desirable physical characteristics, including flow rate, angle of repose, hardness, friability, and disintegration time that comply with requirements. In addition, natural binders such as gelatin, starch, and cellulose demonstrate comparable performance to synthetic binders in producing high-quality tablets. These materials offer advantages in terms of biocompatibility and environmental sustainability. However, variations in composition and hygroscopic properties remain challenges in standardization and long-term stability, which are closely related to Stabilitas Obat. Overall, the proper selection and combination of fillers and binders in wet granulation significantly influence the quality of granules and tablets. Therefore, further optimization is necessary to ensure consistencyandstabilityduringstorage.